Intestinal parasitic infections in Malaysian school children - Sinniah, B.; Rohela, M.; Ibrahim, J.; Amritpal, S.; Ding, K.S.; Lee, K.Y.; Sanjeevan, R.; Sim, S.T.; Elangowan, S. (2010)
Intestinal parasitic infections are still a major public health problem in most developing countries. Previous studies have indicated a high prevalence in Malaysia.